Continuous infusion of midazolam in the treatment of refractory generalized convulsive status epilepticus - Ulvi, H; Yoldas, T; Müngen, B; Yigiter, R (Springer-Verlag, 2002)
We studied the efficacy and safety of midazolam given as a continuous infusion in the treatment of refractory generalized convulsive status epilepticus (RGCSE). We carried out a prospective, open study, in 19 patients (11 men) with RGCSE in the intensive care unit at Firat Medical Center in Elazig. When intravenous administration of 0.3 mg/kg diazepam (three times at 5-min intervals), 20 mg/kg phenytoin, and 20 mg/kg phenobarbital failed to bring the episode under control, patients were administered an intravenous bolus of midazolam (200 mug/kg) followed by a continuous infusion at I mug/kg min. The dose was increased by 1 mug/kg min every 15 min until the episode of seizure was brought under control. The time from beginning of treatment to control of seizures, infusion rate, and side-effects were monitored. The mean age of the patients was 40.4 years (range 16-87 years). The clinical etiology of RGCSE was idiopathic epilepsy (6 cases), anoxic-encephalitis (2), intrahemispheric hematoma due to hemorrhagic stroke (1), cerebral infarct due to ischemic stroke (1), pituitary adenoma (1), post-traumatic epilepsy (1), renal failure (1), tuberculous meningitis (1), and unknown (2). In eighteen (94.7%) patients, seizures were completely controlled in a mean time of 45 min (range, 5-120 min) at a mean infusion rate of 8 mug/kg min (range, 3-21 mug/kg min). In one patient seizures did not stop. Midazolam administration did not cause any significant change in blood pressure, heart rate, oxygen saturation, or respiratory status. The mean time to full consciousness for patients after stopping the infusion was 1.6 hours (range, 2.0-8.5 hours). The mean infusion duration of midazolam was 14.5 hours (range, 12-25 hours). Midazolam is an effective and safe drug to control RGCSE, and may represent a substantial improvement over current therapeutic approaches such as pentobarbital anesthesia.
Keywords: midazolam; anticonvulsants; status epilepticus; neurologic emergencies